Okun’s law in an emerging country: An empirical analysis in Indonesia - Cheng-Wen Lee; Andrian Dolfriandra Huruta (International Entrepreneurship Review, 2019)
Objective: Labor economics policy instruments, such as gross domestic product (GDP) and unemployment are persistent challenges for every country. As an emerging country, Indonesia seeks to reduce unemployment and increase gross domestic product. The aim of this study is to investigate the relationship between GDP and the open unemployment rate in Indonesia starting from 1987 to 2017.